Critical role of particle size and interfacial properties in the visible light induced splitting of water over the nanocrystallites of supported cadmium sulphide - Deshpande, Aparna; Gupta, Narendra M. (International Journal of Hydrogen Energy, 2010)
CdS crystallites of varying size (1 to 5.0 nm) were successfully deposited on the surfaces of polyester and activated charcoal. The size and the texture of these crystallites depended on CdS loading and also on the substrate morphology. These highly dispersed photocatalysts displayed a pyramidal trend in activity for visible light induced splitting of water molecules, similar to that reported for the heterogeneous catalytic reactions over supported noble metals. Thus, the CdS particles of similar to 2.5 nm size gave rise to maximum rate of H(2) evolution as compared to the particles of either smaller or of larger size. The particles of <1.5 nm diameter were of poor crystallinity and displayed a significant Q-size effect on the absorption edge. Our study provides direct evidence for the structure sensitivity of photocatalytic dissociation of water over supported semiconductor nanocrystallites, where the particle size and the interfacial microstructural defects played a vital role. (C) 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: CdS nanocrystallites; Interfacial defects; Photocatalysis; Structural sensitivity; water splitting

Covalent organic framework-cadmium sulfide hybrid as a prototype photocatalyst for visible-light-driven hydrogen production - Thote, Jayshri; Aiyappa, Harshitha Barike; Deshpande, Aparna; Diaz, David Diaz; Kurungot, Sreekumar; Banerjee, Rahul (Chemistry A-European Journal, 2014)
CdS nanoparticles were deposited on a highly stable, two-dimensional (2D) covalent organic framework (COF) matrix and the hybrid was tested for photocatalytic hydrogen production. The efficiency of CdS-COF hybrid was investigated by varying the COF content. On the introduction of just 1 wt% of COF, a dramatic tenfold increase in the overall photocatalytic activity of the hybrid was observed. Among the various hybrids synthesized, that with 10 wt% COF, named CdS-COF (90: 10), was found to exhibit a steep H2 production amounting to 3678 mmolh(-1) g(-1), which is significantly higher than that of bulk CdS particles (124 mmolh(-1)g(-1)). The presence of a p-conjugated backbone, high surface area, and occurrence of abundant 2D hetero-interface highlight the usage of COF as an effective support for stabilizing the generated photoelectrons, thereby resulting in an efficient and high photocatalytic activity.
Keywords: charge transfer; covalent organic frameworks; hybrid materials; hydrogen production; Photocatalysis